PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO DAN BOOKWIDGETS PADA MATERI DAULAH MUGHAL KELAS XI DI MAN KOTA PALANGKA RAYA - Nurlisda,, Nurlisda; Husin, Muhammad Maulana; Arrazin, Muhammad Zaki; Azis, Abdul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to develop learning video media to increase the concentration and understanding of class XI-H students in Man Kota Palangka Raya regarding the Mughal Daula material. and development (RD), Development model 4-D model with data collection techniques in this research namely interviews, observation, documentation and questionnaires. Questionnaires were given to media experts, material experts, SKI teachers and students. The collected data was analyzed using quantitative descriptive analysis techniques. The results of this research show that at the define stage the researcher carried out needs analysis, student analysis and material analysis. The second stage is Design, designing the initial media draft in the form of a storyboard. The third stage of development, the resulting product is a video with the results of material expert validation obtained a validity percentage of 91,7% with the criteria "very feasible" and the validation results from media experts obtained a validity percentage of 89% with the criteria "very worthy". The teacher's response received an assessment of 85% in the "Very Good" and trial categories 30 students got a score of 90,5% in the "Good" category. So it can be said that students feel happy and interested. Finally, Dessiminate, the resulting video can be downloaded on WhatsApp and distributed to students through the class XI-H group The research can conclude that the development of Mughal history video media will help increase the concentration of students' enthusiasm at MAN Palangka Raya City.